State, competition and industrial change in Ireland 1991-1999 - O Riain, Sean (Economic & Social Studies, 2004)
As job losses increased rapidly in 2003 amid calls for increased competitiveness, it becomes all the more crucial to understand the character and causes of such industrial upgrading that did occur in Ireland in the 1990s. This paper argues that despite a continuing reliance on foreign investment, there were significant elements of local industrial upgrading within the Irish economy in the 1990s. Contrary to perspectives which emphasise the learning effects associated with foreign firms, the paper suggests that such upgrading only emerged when and where local and national institutions were established to support relations of innovation and organisational development. The current difficulties in the Irish economy can be traced in significant part to the failure to deepen and extend this emergent system of innovation. The emphasis on `competitiveness? in contemporary policy debate threatens to undermine the public investment, social relations and collective institution building that have been, and will continue to be, central to industrial upgrading in Ireland.
Keywords: Industrial policy; Competitiveness; Industrial change; Ireland; Innovation; Government policy